Running effective meetings for dummies - Allen, Joseph A., 1981-; Reed, Karin M. (For Dummies, 2022)
Turn meetings into the best part of your day with this actionable, step-by-step guide Brainstorming meetings. Team meetings. Stakeholder meetings. Zoom meetings. Hybrid meetings. Most of us are part of more meetings than we can even count. And how many of these meetings are actually productive and valuable? Running Effective Meetings For Dummies shows you how to plan, guide, and run a great meeting, whether you're doing it face-to-face, fully virtual, or a combination of both. Authors Dr. Joseph Allen, industrial and organizational psychologist, and Emmy-award winning communications expert Karin Reed team up to walk you through the steps you need to take to make your next meeting your best one yet. You'll learn about: The different kinds of meetings and what each is supposed to accomplish How to prep for a great meeting and set the expectations of all the participants How to be an effective leader by guiding discussion during the actual meeting itself Effective follow-up and evaluation to keep your momentum and continually improve your meetings Stop enduring meeting-fatigue and start making meetings the fun, productive, and engaging events they're supposed to be. Grab a copy of Running Effective Meetings For Dummies today!.